Trade-Offs between Avoidance of Noxious Electric Shock and Avoidance of Bright Light in Shore Crabs Are Consistent with Predictions of Pain - Stuart Barr; Robert W. Elwood (Animals, 2024)
The suggestion that decapod crustaceans might experience pain has been dismissed by some authors who claim decapods only respond to noxious stimuli by nociceptive reflexes. Because reflexes do not require complex neuronal processing, but pain does, demonstrating reflex responses to noxious stimuli would not support the case for pain. Here, we report an experiment in which shore crabs are repeatedly placed in a light area (20 trials), but the animals can avoid the light by moving to a dark shelter. However, some crabs received an electric shock of 6 or 12 volts each time they entered the shelter. Those receiving either level of shock swiftly reduced their use of shelters and remained in the light. However, the magnitude of shelter avoidance was influenced by the brightness of the arena and the intensity of the shock. Shelter use was subsequently reduced to a greater extent if the shock level was high and the light intensity low. That is, crabs traded their avoidance of shock for their avoidance of bright light. Further, these animals showed avoidance learning and demonstrated activities suggesting anxiety, such as contact with the tank wall in the light area and increased latency to enter shelters when making the decision to enter the shelter if they had received shock in earlier trials. These results fulfil three key behavioural criteria for pain and, thus, are consistent with the idea that decapods can experience pain.